First finding of the shrimp genus Harperalpheus Felder & Anker, 2007 in the eastern Pacific, with description of a new species from Bahía Málaga, Colombia (Malacostraca: Decapoda: Alpheidae) - Anker, Arthur; Lazarus, Juan Felipe (Zootaxa, 2017)
A new infaunal species of the rare alpheid genus Harperalpheus Felder & Anker, 2007 is described from Bahía Málaga, Pacific coast of Colombia, based on single, incomplete holotype specimen. Harperalpheus leptodactylus sp. nov. may be easily separated from the western Atlantic type species and only other species of the genus, H. pequegnatae Felder & Anker, 2007, by several morphological characters on the first and fifth pereiopod, as well as on the antennular peduncle.